2020
DOI: 10.2217/epi-2019-0280
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Map Genes Can be Critical in Determining the Methylome of Intracranial Aneurysm Patients

Abstract: Aim: Intracranial aneurysm is often asymptomatic until the time of rupture. Elevated homocysteine is reported in vascular diseases. Identifying early events in homocysteine metabolism through methylation map genes may prevent fatality. Materials & methods: In the present study, we investigated the role of variants in methylation map genes in ethnically matched 480 individuals that can influence the homocysteine levels and promote development of aneurysm. Results: The study demonstrates that the genetic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Preclinical evidence suggests a methionine-rich diet may correlate with an elevated risk and expedited formation of IA, 25 and specific genetic variants of the homocysteine cycle have been linked with an increased IA risk. 26 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical evidence suggests a methionine-rich diet may correlate with an elevated risk and expedited formation of IA, 25 and specific genetic variants of the homocysteine cycle have been linked with an increased IA risk. 26 27 …”
Section: Discussionmentioning
confidence: 99%
“…Preclinical evidence suggests a methionine-rich diet may correlate with an elevated risk and expedited formation of IA, 25 and specific genetic variants of the homocysteine cycle have been linked with an increased IA risk. 26,27 Retrospective studies offer contradictory results. 29 identified an association between homocysteine and IA patients [OR 2.2 (95%CI 1.19-4.06)], but both patients and controls exhibited exceptionally high homocysteine levels.…”
Section: Intracranial Aneurysmmentioning
confidence: 99%
“…In the development of cerebrovascular disease,DNA methylation may trigger lesions by altering the expression levels of genes related to vasoconstriction or vasoproliferation, which in turn affects changes in the levels of proteins related to vascular stability (He et al, 2022 ). DNA methylation is closely associated with the risk of IA (Nikkola et al, 2015 ; Zhou et al, 2017 ; Shafeeque et al, 2020 ; Wang et al, 2021 ). Kim et al’s study (Kim et al, 2022 ) showed that different genes with DNA methylation can be useful biomarkers for the accurate diagnosis of delayed cerebral ischemia after aneurysmal subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is closely associated with the risk of IA (Nikkola et al, 2015;Zhou et al, 2017;Shafeeque et al, 2020;Wang et al, 2021). Kim et al's study (Kim et al, 2022) showed that different genes with DNA methylation can be useful biomarkers for the accurate diagnosis of delayed cerebral ischemia after aneurysmal subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…There are few IA biomarkers; these include plasma total homocysteine (tHcy), 6 which remains controversial. 7 8 tHcy is an amino acid generated by the metabolism of dietary methionine and is sensitive to vitamin B 12 , folate and various lifestyle factors.…”
Section: Introductionmentioning
confidence: 99%